2021
DOI: 10.1097/hjh.0000000000002837
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-29a suppressed the migration and invasion of trophoblasts by directly targeting LOXL2 in preeclampsia

Abstract: Objective: Preeclampsia is a pregnancy-specific disorder that is a major cause of maternal and foetal morbidity and mortality, with a prevalence of 6-8% of pregnancies. Although the downregulation of lysyl oxidase (LOX) and LOX-like protein 2 (LOXL2), which leads to reduced trophoblast cell migration and invasion through activation of the TGF-b1/Smad3/collagen pathway, is relevant to preeclampsia, the mechanisms regulating differences in the gene expression of LOX and LOXL2 in placentas are not yet understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…MicroRNAs have been implicated in the progression of normal physiological processes such as pregnancy, as well as in pathological conditions such as cardiovascular diseases, cancer, viral infections, and PE. MicroRNAs post-transcriptionally regulate the expression of VEGFR-2 in normal and pathological conditions [ 18 , 111 ]. Figure 3 explores microRNA regulation of VEGFR-2 in PE, HIV, and SARS-CoV-2 infection.…”
Section: The Involvement Of Vegfr-2-specific Micrornas In Preeclampsi...mentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs have been implicated in the progression of normal physiological processes such as pregnancy, as well as in pathological conditions such as cardiovascular diseases, cancer, viral infections, and PE. MicroRNAs post-transcriptionally regulate the expression of VEGFR-2 in normal and pathological conditions [ 18 , 111 ]. Figure 3 explores microRNA regulation of VEGFR-2 in PE, HIV, and SARS-CoV-2 infection.…”
Section: The Involvement Of Vegfr-2-specific Micrornas In Preeclampsi...mentioning
confidence: 99%
“…MiR-15b, miR-126, miR-29a, and miR-16 are dysregulated in PE, HIV infection, and COVID-19 and influence VEGFR-2 mRNA both directly and indirectly ( Table 1 ) [ 18 , 19 , 111 , 112 , 113 , 114 ]. It was reported that miR-15b is downregulated in PE and HIV but upregulated in COVID-19 [ 18 , 112 ].…”
Section: The Involvement Of Vegfr-2-specific Micrornas In Preeclampsi...mentioning
confidence: 99%
See 1 more Smart Citation